The Participation of Personnel from Three Sectors in Cultural Tourism Management in Maha Sarakham Province - โสภา, ณรงค์ฤทธิ์ (Chophayom Journal, 2019)
The objectives of the survey research were to study the participation and needs for the participation of the governments sectors, private sectors and public sectors in cultural tourism management in Maha Sarakham Province, The sample subjects of the study were one hundred and sixty four participants. They were selected by propostional stratefied random sampling and simple random sampling.The data was collected by three sets of a 5-point rating questionnaire. The data was analyzed and tabulated by means of statistical procedures: percentage, mean and standard deviation. The research findings showed that the overall participation of the personnel from the government sectors in cultural tourism management in Maha Sarakham Province was at a high level ( =4.25 S.D.=.55). 2) The overall participation of the personnel from the private sectors and public sectors in cultural tourism management in Maha Sarakham Province was at a moderate level ( =3.10 S.D.=.64) and ( =3.20 S.D.=.53). 3) The overall need of the personnel from the government, private and public sectors for the cultural tourism management was a high level ( =4.25 S.D.=.56) ( =4.2 S.D.=.61) and ( =4.24 S.D.=.45) respectively. Keywords : Participation, Personnel from Three Sections, Cultural Tourism Management, Maha Sarakham Province